Topical formulations of miltefosine for cutaneous leishmaniasis in a BALB/c mouse model. (27th May 2016) - Van Bocxlaer, Katrien; Yardley, Vanessa; Murdan, Sudaxshina; Croft, Simon L.
Abstract: Cutaneous leishmaniasis (CL) is caused by several species of the protozoan parasite Leishmania and affects approximately 10 million people worldwide. Currently available drugs are not ideal due to high cost, toxicity, parenteral administration and suboptimal efficacy. Miltefosine is the only oral treatment (Impavido®) available to treat CL, given over a period of 28 days with common side effects such as vomiting and diarrhoea. Objective: To explore the local application of miltefosine as a topical formulation to enhance activity and reduce the drug's adverse effects. Methods: The antileishmanial activity of miltefosine was confirmed in vitro against several Leishmania species. The permeation of miltefosine, in different solvents and solvent combinations, through BALB/c mouse skin was evaluated in vitro using Franz diffusion cells. The topical formulations which enabled the highest drug permeation or skin disposition were tested in vivo in BALB/c mice infected with L. major . Key findings: The overall permeation of miltefosine through skin was low regardless of the solvents used. This was reflected in limited antileishmanial activity of the drug formulations when applied topically in vivo . All topical formulations caused skin irritation. Conclusions: We conclude that miltefosine is not an appropriate candidate for the topical treatment of CL.